Performance of today's dual energy CT and future multi energy CT in virtual non‐contrast imaging and in iodine quantification: A simulation study. Issue 7 (24th June 2015) - Faby, Sebastian; Kuchenbecker, Stefan; Sawall, Stefan; Simons, David; Schlemmer, Heinz‐Peter; Lell, Michael; Kachelrieß, Marc
Abstract : Purpose: To study the performance of different dual energy computed tomography (DECT) techniques, which are available today, and future multi energy CT (MECT) employing novel photon counting detectors in an image‐based material decomposition task. Methods: The material decomposition performance of different energy‐resolved CT acquisition techniques is assessed and compared in a simulation study of virtual non‐contrast imaging and iodine quantification. The material‐specific images are obtained via a statistically optimal image‐based material decomposition. A projection‐based maximum likelihood approach was used for comparison with the authors' image‐based method. The different dedicated dual energy CT techniques are simulated employing realistic noise models and x‐ray spectra. The authors compare dual source DECT with fast kV switching DECT and the dual layer sandwich detector DECT approach. Subsequent scanning and a subtraction method are studied as well. Further, the authors benchmark future MECT with novel photon counting detectors in a dedicated DECT application against the performance of today's DECT using a realistic model. Additionally, possible dual source concepts employing photon counting detectors are studied. Results: The DECT comparison study shows that dual source DECT has the best performance, followed by the fast kV switching technique and the sandwich detector approach. Comparing DECT with future MECT, the authors found noticeable material image quality improvements for an ideal photon counting detector; however, a realistic detector model with multiple energy bins predicts a performance on the level of dual source DECT at 100 kV/Sn 140 kV. Employing photon counting detectors in dual source concepts can improve the performance again above the level of a single realistic photon counting detector and also above the level of dual source DECT. Conclusions: Substantial differences in the performance of today's DECT approaches were found for the application of virtual non‐contrast and iodine imaging. Future MECT with realistic photon counting detectors currently can only perform comparably to dual source DECT at 100 kV/Sn 140 kV. Dual source concepts with photon counting detectors could be a solution to this problem, promising a better performance.